Pathological features in marine birds affected by the prestige's oil spill in the north of Spain - Balseiro, Ana; Espí, Alberto; Marquez, I.; Pérez Pérez, Valentín; Ferreras, Mª del Carmen; García Marín, Juan Francisco; Prieto, J. M. (Wildlife Disease Association, 2005)
8 páginas, 4 Figuras, 2 tablas. A total of 2,465 seabirds, mainly common murres (Uria aalge), razorbills (Alca torda), and puffins (Fratercula arctica) that beached in the northwestern part of Spain after the >Prestige> oil spill on 19 November 2002 were examined by pathological methods. Birds were divided into three groups: dead birds with the body covered (group 1) or uncovered (group 2) by oil and birds recovered alive but which died after being treated at a rescue center (group 3). The main gross lesions were severe dehydration and emaciation. Microscopically, hemosiderin deposits, related to cachexia and/or hemolytic anemia, were observed in those birds harboring oil in the intestine. Severe aspergillosis and ulcers in the ventriculus were found only in group 3 birds, probably because of stress associated with attempted rehabilitation at the rescue center. The mild character of the pathological changes suggests that petroleum oil toxicosis causes multiple sublethal changes that have an effect on the ability of the birds to survive at sea, especially weak and young, inexperienced animals. Dehydration and exhaustion seem to be the most likely cause of death. Peer Reviewed